2017
DOI: 10.3389/fneur.2017.00244
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-10 in Acute Brain Injuries

Abstract: Interleukin-10 (IL-10) is an important anti-inflammatory cytokine expressed in response to brain injury, where it facilitates the resolution of inflammatory cascades, which if prolonged causes secondary brain damage. Here, we comprehensively review the current knowledge regarding the role of IL-10 in modulating outcomes following acute brain injury, including traumatic brain injury (TBI) and the various stroke subtypes. The vascular endothelium is closely tied to the pathophysiology of these neurological disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(139 citation statements)
references
References 163 publications
(246 reference statements)
5
119
1
14
Order By: Relevance
“…The findings support our recent research, which showed that IL‐10 contributes to macrophage alternative activation, hematoma resolution, and improved neurologic function in an animal model of ICH . Interestingly, preclinical and clinical studies about the role of IL‐10 in acute brain injury yielded opposite results . Further research is needed to investigate whether the changes in the immune system identified in this study could be used as a target for the treatment of ICH.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings support our recent research, which showed that IL‐10 contributes to macrophage alternative activation, hematoma resolution, and improved neurologic function in an animal model of ICH . Interestingly, preclinical and clinical studies about the role of IL‐10 in acute brain injury yielded opposite results . Further research is needed to investigate whether the changes in the immune system identified in this study could be used as a target for the treatment of ICH.…”
Section: Discussionsupporting
confidence: 86%
“…17 Interestingly, preclinical and clinical studies about the role of IL-10 in acute brain injury yielded opposite results. 83 Further research is needed to investigate whether the changes in the immune system identified in this study could be used as a target for the treatment of ICH. Instead of using the neutrophil-to-lymphocyte ratio reported in the previous reports, 84,85 we analyzed changes in the granulocyte-to-lymphocyte ratio (GLR) in this study because neutrophils account for a large proportion of granulocytes.…”
Section: F I G U R E 4 Influence Of Time From Symptom Onset To Mis Lmentioning
confidence: 99%
“…In SAH, IL-10 levels were significantly elevated after SAH and were associated with general cerebral edema [20], which is a prognostic factor for poor clinical outcome in patients. However, detailed preclinical and clinical studies investigating the association between serum IL-10 levels and post-SAH infections are still lacking [21]. The current study was planned to investigate contribution of systemic IL-10 levels during early and delayed brain injury towards the development of post-SAH infections and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…TNF‐α, IL‐1β and IL‐6 are the most relevant activating cytokines known to act on the CNS; these molecules mediate information between cells and behave like a network, since they can activate cells to produce other cytokines and inflammatory mediators, and promote immune cell infiltration into the brain parenchyma (Colombo and Farina, 2016; Jensen et al, 2013). IL‐10, in contrast, has the ability to attenuate neuroinflammation by suppressing inflammatory pathways and promoting cellular repair processes (Garcia et al, 2017; Strle et al, 2001).…”
Section: Discussionmentioning
confidence: 99%